Perancangan Aplikasi Harga Cerdas Berbasis Android - Very Karnadi; Sunarsan Sitohang (LPPM Universitas Putera Batam, 2020)
The increasing number of customers at minimarkets creates problems in the convenience and effectiveness of the shopping process at the minimarket. The problem of information regarding the data of goods is often complained of by customers, such as there is often a difference in the price listed on the shelf with the price at the checkout and the lack of information makes customers busy looking for employees to ask about item details. The purpose of this study is to produce an android-based cashier application to help minimarket visitors to see information about the price of goods, the amount of groceries and the total shopping to be paid at the cashier. In addition, this application also includes information on expired items so that customers can find comfort in the forest. This application has a barcode scanning feature where each item is scanned and can view item details such as id, name, dimensions, quantity, color, price, and images of goods and expiration date. This mini market application is based on android which is integrated on a server via the internet and is supported by the MYSQL Database. By using a system like this, customer comfort and satisfaction when it is expected will increase and become more value from the minimarket side itself so that it helps cashiers in the process of managing sales data more effectively, efficiently and accurately so that customers get comfort in shopping activities and do not feel suspicious about the cheating of convenience stores.